Chronic structural adaptations of the shoulder and elbow are correlated in professional baseball pitchers - Paul, R. W.; Osman, A.; Nazarian, L. N.; Ciccotti, M. G.; Cohen, S. B.; Erickson, B. J.; Buchheit, P.; Rauch, J.; Osbahr, D. C.; Thomas, S. J. (The American Journal of Sports Medicine, 2025)
Background: Pitchers with deficits in total shoulder rotation range of motion (ROM) are 2.6 times more likely to experience an elbow injury. Despite the effects of shoulder ROM on elbow injury, it is currently unclear whether specific tissue adaptations of the shoulder relate to the tissue adaptations of the elbow in baseball pitchers.